2023
DOI: 10.3390/ijms24054296
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the (Auto)Reactive T Cells in Rheumatoid Arthritis According to the Immune Epitope Database

Abstract: T cells are known to be involved in the pathogenesis of rheumatoid arthritis (RA). Accordingly, and to better understand T cells’ contribution to RA, a comprehensive review based on an analysis of the Immune Epitope Database (IEDB) was conducted. An immune CD8+ T cell senescence response is reported in RA and inflammatory diseases, which is driven by active viral antigens from latent viruses and cryptic self-apoptotic peptides. RA-associated pro-inflammatory CD4+ T cells are selected by MHC class II and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…A variety of cytokines released by different T cell subsets are involved in the inflammatory microenvironment of RA ( 21 ).For example, Th17 cells can promote macrophages, synoviocytes and other cells to secrete a large number of inflammatory factors such as IL-1β and IL-6 by producing IL-17 and also contribute to the production of CXCL1, CXCL2, CXCL8 and other chemokines ( 4 , 22 ). Overactivation of T cells is a factor that triggers maintains RA ( 1 ). Therefore, understanding the molecular mechanisms associated with T cells from multiple aspects will help to discover more immunotherapy methods for RA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of cytokines released by different T cell subsets are involved in the inflammatory microenvironment of RA ( 21 ).For example, Th17 cells can promote macrophages, synoviocytes and other cells to secrete a large number of inflammatory factors such as IL-1β and IL-6 by producing IL-17 and also contribute to the production of CXCL1, CXCL2, CXCL8 and other chemokines ( 4 , 22 ). Overactivation of T cells is a factor that triggers maintains RA ( 1 ). Therefore, understanding the molecular mechanisms associated with T cells from multiple aspects will help to discover more immunotherapy methods for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Rheumatoid arthritis (RA) is a commonly occurring autoimmune disease that affects 0.5–1% of the world’s population ( 1 ). The mechanism of RA has not yet been elucidated, and an effective cure is still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The HLA-DRB1 SE overrepresentation in RA was historically defined through the demonstration that the presence of HLA-DRB1 risk alleles harboring SE leads to the non-proliferative state in co-cultured lymphocytes from RA patients, which was not the case when using lymphocytes from healthy subjects ( 25 28 ). Next, it was reported that HLA-DRB1 SE represented the most predominant genetic risk factor associated with RA ( 29 ), and this overrepresentation was observed in 55% of the FDR from RA patients as compared to 43% in the HC group from North America ( 30 ).…”
Section: Discussionmentioning
confidence: 99%